Qualitative analysis of mapping systems in the Internet architectures based on identifier/locator separation. Issue 1 (2nd January 2016) - Hong, Jungha; You, Taewan; Jung, Heeyoung
Abstract : The current Internet has several known challenges, such as routing scalability, mobility, multihoming, traffic engineering, etc. due to the overloaded semantics of IP address, i.e. it is used as a node identifier (ID) and a node locator (LOC). Thus, the research community has redesigned the Internet architecture based on ID/LOC separation to overcome the limitations of the current Internet. In all Internet architectures based on ID/LOC separation, ID to LOC mapping system is necessarily required to bind ID and its LOC, since ID is no longer dependent to its LOC logically or physically. Thus, how to design the mapping system is a key challenge in ID/LOC separation architecture. In this paper, we analyse qualitatively the mapping systems proposed in ID/LOC separation architectures to provide insights into designing a new mapping system. The main contribution in this paper is that we categorise ID to LOC mapping systems according to the mapping server structure and provide the pros and cons of the mapping systems belonging to each category. Based on our qualitative analysis, we also examine intuitively if the mapping systems in each category satisfy their requirements.